Temporal hampering of thyroid hormone synthesis just before hatching impeded the filial imprinting in domestic chicks - Serizawa, Shouta; Aoki, Naoya; Mori, Chihiro; Fujita, Toshiyuki; Yamaguchi, Shinji; Matsushima, Toshiya; Homma, Koichi J. (Frontiers in Physiology, 2023)
Thyroid hormones play a critical role in the initiation of the sensitive period of filial imprinting. The amount of thyroid hormones in the brains of chicks increases intrinsically during the late embryonic stages and peaks immediately before hatching. After hatching, a rapid imprinting-dependent inflow of circulating thyroid hormones into the brain occurs via vascular endothelial cells during imprinting training. In our previous study, inhibition of hormonal inflow impeded imprinting, indicating that the learning-dependent inflow of thyroid hormones after hatching is critical for the acquisition of imprinting. However, it remained unclear whether the intrinsic thyroid hormone level just before hatching affects imprinting. Here, we examined the effect of temporal thyroid hormone decrease on embryonic day 20 on approach behavior during imprinting training and preference for the imprinting object. To this end, methimazole (MMI; a thyroid hormone biosynthesis inhibitor) was administered to the embryos once a day on days 18–20. Serum thyroxine (T4) was measured to evaluate the effect of MMI. In the MMI-administered embryos, the T4 concentration was transiently reduced on embryonic day 20 but recovered to the control level on post-hatch day 0. At the beginning of imprinting training on post-hatch day 1, control chicks approached the imprinting object only when the object was moving. In the late phase of training, control chicks subsequently approached towards the static imprinting object. On the other hand, in the MMI-administered chicks, the approach behavior decreased during the repeated trials in the training, and the behavioral responses to the imprinting object were significantly lower than those of control chicks. This indicates that their persistent responses to the imprinting object were impeded by a temporal thyroid hormone decrease just before hatching. Consequently, the preference scores of MMI-administered chicks were significantly lower than those of control chicks. Furthermore, the preference score on the test was significantly correlated with the behavioral responses to the static imprinting object in the training. These results indicate that the intrinsic thyroid hormone level immediately before hatching is crucial for the learning process of imprinting.